Centrifuge modelling of pipe-soil interaction in clay with crust layer. (January 2021) - Hou, Zhechen; Sahdi, Fauzan; Gaudin, Christophe; Randolph, Mark
Abstract: Seabed in regions, such as the Gulf of Guinea and North West Shelf of Australia, may exhibit a crust layer where the undrained shear strength can be an order of magnitude higher than that of the immediately underlying sediment. This can complicate design of steel catenary risers, where fatigue depends on the cyclic vertical stiffness of the pipe-soil interaction. Potential punch-through of the riser into the underlying soft soil may invalidate design assumptions based on the pipe-soil stiffness within the crust layer. The long-term evolution of pipe-soil stiffness within the crust layer, which exhibits similar properties to an over-consolidated soil, is also poorly understood. This paper describes centrifuge model tests undertaken in a clay sample with a crust layer, simulating the punch-through process of a pipe under load control and investigating the pipe-soil stiffness during long-term cyclic loading tests under displacement control. Results confirm that the potential for punching-through the crust layer depends strongly on the relative ratio of pipe diameter to crust layer thickness. The long-term evolution of pipe-soil stiffness showed a steady increase after an initial remoulding stage in contractile soils (normally consolidated and lightly over-consolidated), but a steady reduction in the heavily over-consolidated, more dilatant, crust. The magnitude of pipe-soil stiffness changes (during both remoulding and reconsolidation) is governed by the over-consolidation ratio of the soil and the amplitude of the cyclic displacements. This study provides insights on the relevant cyclic stiffness to consider when assessing SCR fatigue life in over-consolidated soils and soils exhibiting a superficial crust layer. Highlights: Results from a centrifuge test programme simulating the response of an element of an SCR at the touchdown zone are reported. The long-term SCR-soil stiffness evolution is shown to depend on the soil overconsolidation ratio (OCR). A critical state framework is used to understand the effects of OCR and cyclic amplitude on SCR-soil stiffness evolution.